(untitled) (The Research of Medical Science Review, 2025)
Background: Surgical Site Infection (SSI) leads to adverse outcomes, with its frequency influenced by factors like age, blood loss, transfusion, type and duration of surgery. The controversy in existing literature prompted this study to clarify these associations for improved future practice in SSI management. Objectives: 1) To determine the frequency of surgical site infection in patients presenting for surgery at General Surgery Department, Divisional Head Quarter Hospital Mirpur, AJK. 2) To determine frequency of SSI based on duration of surgery, blood transfusion, intra-operative blood loss and type of surgery. Duration: Six months w.e.f 11-11-2023 to 10-05-2023 Methodology: After approval from the hospital review committee, 150 adult patients meeting the inclusion criteria were enrolled. Informed consent was obtained, and demographics recorded. Each patient underwent surgery under general anesthesia. Surgery duration, blood loss, and Hb levels were noted. Blood transfusion was administered if necessary. Standard antibiotics were given, and patients were discharged. Follow-up on day 10 assessed SSI, managed by duty staff, with confounding variables controlled by exclusion. Results: The study included 150 participants with a mean age of 41.7 ± 12.24 years. Most were aged 41-60 years (54.7%, n=68), and 51.3% (n=82) were male. Surgical procedures were 58.7% appendectomy (n=88), 24.0% exploratory laparotomy (n=36), and 17.3% hernia repair (n=26). The average surgery duration was 103.8 ± 20.86 minutes, with 28% lasting 2 hours or more. Intraoperative blood loss averaged 128.47 ± 122.25 ml, and 8.7% required blood transfusions. SSI occurred in 32.7% of patients, particularly in longer surgeries, significant blood loss, and emergency cases. Conclusion: In conclusion, this study found that 32.7% (n=49) of patients developed SSI. Factors such as age, gender, procedure type, surgery duration, blood loss, transfusion, and surgery nature influenced SSI incidence, emphasizing the need for targeted preventive measures.